La necesidad de modernizar la relación laboral como mecanismo para fomentar el empleo en el Ecuador en el año 2021. - Ríos Hervas, Jina Pamela (2022)
In the present investigative work, I will make known about the need to modernize the labor relationship as a mechanism to promote employment in Ecuador, in which, according to Article 1 of the Labor Code, we find the relationships between workers and employers typified, the various modalities and working conditions. It is important to detail as background on the topic addressed that, on August 5, 1938, the first legal text that regulated labor relations was published and contained provisions on eviction, rest days, work day, employment contract, among others. In this way, it is proposed that thanks to this research, employers and workers know the public policies, ministerial agreements and legal reforms, international agreements and conventions that were created to modernize the employment relationship to promote employment in Ecuador. At the same time, the Constitution of the Republic of Ecuador in Article 327 establishes that the employment relationship between workers and employers must be direct and bilateral, that is, it guarantees that all types of employment contract must be made between two parties and acquire obligations and rights. The methodology of this research is qualitative of documentary or bibliographical analysis since I will obtain information from reliable sources in: legal journals, laws, codes, among others, therefore, this project is important both in the social and labor spheres. Finally, as expected results, it is in a positive way for the benefit of the whole society so that they are aware of the need to modernize the employment relationship between employers and workers and thus guarantee the right to work as a Constitutional right